Building machine-readable knowledge representations for Turkish sign language generation - Eryiğit, Cihat; Köse, Hatice; Kelepir, Meltem; Eryiğit, Gülşen (Knowledge-based systems, 2016)
This article proposes a representation scheme for depicting the Turkish Sign Language (TİD) electronically for use in an automated machine translation system whose basic aim is to translate the Turkish primary school educational materials to TİD. The main contribution of the article is the introduction of a machine-readable knowledge representation for TİD for the first time in the literature. Like many resource-poor languages, TİD lacks electronic language resources usable in computerized systems. The utilization of the proposed scheme for resource creation is also provided in this article by two means: an interactive online dictionary platform for TİD and an ELAN add-on for corpus creation.